Effects of multiple chondroitinase ABC applications on tissue engineered articular cartilage - Natoli, Roman M. (2009)
Increasing tensile properties and collagen content is a recognized need in articular cartilage tissue engineering. This study tested the hypothesis that multiple applications of chondroitinase ABC (C-ABC), a glycosaminoglycan (GAG) degrading enzyme, could increase construct tensile properties in a scaffold-less approach for articular cartilage tissue engineering. Developing constructs were treated with C-ABC at 2 wks, 4 wks, or both 2 and 4 wks. At 4 and 6 wks, construct sulfated GAG composition, collagen composition, and compressive and tensile biomechanical properties were assessed, along with immunohistochemistry (IHC) for collagens type I, II, and VI, and the proteoglycan decorin. At 6 wks, the tensile modulus and ultimate tensile strength of the group treated at both 2 and 4 wks were significantly increased over controls by 78% and 64%, reaching values of 3.4 and 1.4 MPa, respectively. Collagen concentration also increased 43%. Further, groups treated at either 2 wks or 4 wks alone also had increased tensile stiffness compared to controls. Surprisingly, though GAG was depleted in the treated groups, by 6 wks there were no significant differences in compressive stiffness. IHC showed abundant collagen type II and VI in all groups, with no collagen type I. Further, decorin staining was reduced following C-ABC treatment, but returned during subsequent culture. The results support the use of C-ABC in cartilage tissue engineering for increasing tensile properties.